Rebel Seoul - Oh, Axie (New York : Tu Books, an imprint of Lee & Low Books Inc., 2017)
In 2199 in the Neo State of Korea, eighteen-year-old Jaewon is partnered with supersoldier Tera, but their evolving love is threatened when Jaewon must choose among conflicting loyalties--to the totalitarian government that promises to end all war, the nationalist rebels his father followed, or the crime syndicate staging a coup.
Keywords: Robots -- Juvenile fiction; Soldiers -- Juvenile fiction; War stories; Love in adolescence -- Juvenile fiction; Totalitarianism -- Juvenile fiction; Robots -- Fiction; Soldiers -- Fiction; War -- Fiction; Love -- Fiction; Totalitarianism -- Fiction; Science fiction; Korea -- Juvenile fiction; Korea -- Fiction